CMT performance optimization algorithm based on union prediction of bandwidth and round trip time - LI Wen; WANG Wen-bo; JING Xiao-jun; LIU Wen; ZHANG Chao (工程科学学报, 2015)
Concurrent multipath transfer (CMT) uses the stream control transmission protocol's (SCTP) multihoming feature to distribute data across multiple end-to-end paths in a multihomed SCTP association. Due to the disparity of multipaths, it is facing a great challenge to solve the disorder of received data packets. In order to lighten the reordering degree and then to improve the through-put performance, we need to estimate the bandwidth and round trip time (RTT) of the real-time paths as exactly as possible. In this paper, we use the extended vector Kalman filter to predict the available bandwidth and RTT of each path simultaneously. Based on this, we propose a predictive path selection algorithm for CMT in SCTP. Simulation results show that the path selection algorithm can lessen the data packets disordering by correctly predicting each path's bandwidth and RTT in real time. To bandwidth sensitive scene,the algorithm can converge more quickly than Kalman-CMT and can improve the system total throughput in a certain extent. To time and bandwidth sensitive scene, the algorithm can greatly improve the convergence speed and total throughput than Kalman-CMT.